Interplay Between Glucose Metabolism and Chromatin Modifications in Cancer - Ma, Rui; Wu, Yinsheng; Li, Shanshan; Yu, Xilan (Frontiers in Cell and Developmental Biology, 2021)
Cancer cells reprogram glucose metabolism to meet their malignant proliferation needs and survival under a variety of stress conditions. The prominent metabolic reprogram is aerobic glycolysis, which can help cells accumulate precursors for biosynthesis of macromolecules. In addition to glycolysis, recent studies show that gluconeogenesis and TCA cycle play important roles in tumorigenesis. Here, we provide a comprehensive review about the role of glycolysis, gluconeogenesis, and TCA cycle in tumorigenesis with an emphasis on revealing the novel functions of the relevant enzymes and metabolites. These functions include regulation of cell metabolism, gene expression, cell apoptosis and autophagy. We also summarize the effect of glucose metabolism on chromatin modifications and how this relationship leads to cancer development. Understanding the link between cancer cell metabolism and chromatin modifications will help develop more effective cancer treatments.